Mediation of Organizational Citizenship Behavior, Organizational Culture and Competence on the Performance of Nursing Paramedics at Dr. Ishak Umarella Tulehu Regional General Hospital, Central Maluku Regency - Agusthina Risambessy; Saleh Tutupoho; Pieter N.R. Rehatta (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
Organizational culture is a way of thinking or tradition adopted by all members of the company and new members must learn or at least accept it as part of the company. Given the importance of organizational culture in the company, this study aims to analyze and explain the mediation of Organizational Citizenship Behavior Organizational Culture and Competence on the performance of nursing paramedics. With the research population at the Dr. Ishak Umarella Tulehu Regional General Hospital, Central Maluku Regency. The sampling technique uses purposive sampling where 1. Nursing Paramedics, 2. Graduated from Nursing 3. Have worked for more than 2 years totaling 116 people were sampled. Using the analysis method: Path Analysis Square (PLS) The results of the study prove that: Organizational Culture has a significant effect on the performance of nursing paramedics. Competence has a significant effect on the performance of nursing paramedics. Organizational Citizenship Behavior has a significant effect on the performance of nursing paramedics Organizational culture has a significant effect on Organizational Citizenship Behavior. Competence has a significant effect on Organizational Citizenship Behavior. Organizational culture has a significant effect on employee performance mediated by Organizational Citizenship Behavior, Competence has a significant effect on employee performance mediated by Organizational Citizenship Behavior. Suggestions for subsequent researchers: can examine the variables that have been studied in this study by adding work involvement variables and expanding the research object to several Private Hospitals.